Automatisiertes Record Linkage in prosopographischen Datenbeständen am Beispiel historischer Quellen Leipzigs - Jan Michael Goldberg; Marcel Mernitz (Zeitschrift für digitale Geisteswissenschaften)
In this study, an automated approach to record linkage in prosopographic datasets is presented. It implements numerous genealogical rules for linking individuals. This makes it particularly suitable for datasets that contain a lot of genealogically relevant information about the represented individuals. For this purpose, a standardized data structure is defined into which the input data is to be arranged. The algorithm recognizes entries pertaining to the same persons within this data structure and merges them automatically. In this process, a formalization of genealogical heuristics is performed. The functionality of the algorithm is successfully demonstrated using historical datasets from the city of Leipzig as an example. The program code has been realized in Python and is freely available.